ANALISIS RISIKO PRODUKTIVITAS, HARGA DAN GANTI RUGI POHON KELAPA DI KABUPATEN SERUYAN KALIMANTAN TENGAH - Rusdi Rusdi (Inovasi, 2022)
Coconut is one of the leading agricultural commodities in Seruyan Regency. In household coconut farming, coconut farmers are always faced with risks, especially production and product price risks. The existence of production risks and product prices will affect the economic behavior of coconut farmer households. The aims of this research are: to analyze production risk and product price risk in farming activities, to predict coconut production if there is a risk due to reduction in coconut trees. Farmer households that were sampled in the study totaled 200 households spread across the East Seruyan Hilir District, Seruyan Regency. Results in the study It is known that the average age of coconut plants owned by farmers is 28.79 years, with the oldest coconut being 46 years old. This indicates that the coconut plants in the study area are still classified as productive (<100 years). Based on the distribution, the age of the farmers' coconut plants is dominated by those aged 16-25 years with a percentage of 41.00 percent. While farmers who have coconut plants with age more than 45 years by 1 percent. So that the price of one coconut tree due to the risk of reducing coconut trees, the price of one tree is obtained as follows. Meanwhile, based on Table 12 it is known that the average price of coconuts that is often received (normal price) by coconut farming households is IDR 1,497/item. Meanwhile, the highest average price of coconut ever received by a coconut farmer household was Rp. 1,984/item and the lowest price ever received by an average coconut farmer household was Rp. 1,034. So that compensation for logging coconut trees is Rp. 10,628,700.